Investigating the causes and effects of weak corporate governance that hinder successful performance of African National Development Banks: a case study of Development Bank of Zambia - Kambobe, Chanda (Research of GSB, 2018)
Corporate Governance in African National Development Banks is critical to their success or failure. These Banks have complex corporate governance structures with hierarchies comprising both national government representatives and in some cases the private sector. By focusing on election years this study aimed to show how external interventions from the owners of the Banks (governments) can unduly influence their performance and sustainability. Two causes of weak governance were identified, these were non-independence of the board and broad and unclear mandates. The study shows an increase in lending during election years, suggesting evidence of non-independence of the board signifying undue political influence and wide mandates leading to "mission creeps" usually encouraged by politicians. Non independence has its effects, these were identified as crowding out of the private sector, misallocation of funds and low profitability. A positive correlation was found between the African National Development Bank lending and private bank lending an indication that the African National Development Banks compete with the private banks instead of performing their counter cyclical role, this in turn leads to crowding out the private banks. Misallocat ion of funds is demonstrated by an increase in lending during election years followed by an increase in bad debts two years after the election year, an indication that loans where given to unviable projects. Lastly the study proves the low profitability effect by showing that loans given out are negatively correlated to the Banks profitability, showing a reduction in Bank profitability as more loans are advanced and vice versa. The findings suggest that non-independent boards and wide and broad mandates weaken African National Development Banks corporate governance, negatively affecting their performance and preventing them from executing their mandates effectively.